Kinetic description of ion acoustic waves in a dusty plasma - Pandey, B.P.; Kumar, Susheel (My University, 1995)
A self-consistent model for the description of the ion sound wave in a dusty plasma is given. We show that proper consideration of the ion attachment to the grains gives rise to the dissipation of the ion acoustic wave in a dusty plasma medium. Dissipation rate is proportional to the sum of the electron and twice the ion attachment frequencies.
Keywords: Ion acoustic wave; Charge fluctuations; Dusty plasma